PELATIHAN MERANCANG PEMBELAJARAN TEMATIK BERBASIS HOTS BAGI GURU SD DI KABUPATEN PESAWARAN - Riswandi Riswandi; Een Yayah Haenilah; Lungit Wicaksono; Ismu Sukamto; Mujiyati Mujiyati (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service activity is motivated by the weak understanding of elementary school teachers in HOTS-oriented learning. Therefore, it is necessary to conduct training in designing thematic learning that is oriented towards HOTS. The training is carried out by presenting information, holding responses and group discussions on previously informed material and holding HOTS-based learning tools preparation exercises. The training was attended by elementary school teachers in District of Pesawaran. Based on the results of observations and written tests, the teachers were active in following the material presentation, discussion and preparation of HOTS learning tools. In addition, teachers' understanding has improved. This is evidenced by the pretest and posttest n-gain values of 0.09. However, the increase is not significant. Thus, it can be concluded that the participants' conceptual understanding of HOTS-oriented learning increased. This increase occurred because the previous participants did not really understand the true meaning of HOTS-oriented learning. Through this activity, participants get more detailed and easily accepted knowledge because in addition to presenting the material, the implementer also provides guidance on the development of learning designs. However, there is a need for ongoing technical guidance related to its implementation in classroom learning both online and face-to-face.